(untitled) (Archive of Conferences, 2020)
Today, foreign language lesson in a high school is significantly different from what it was two or three past decades in connection with the development of information technologies and gradual introduction of ICT into educational process. In this case it should be mentioned a special role of information and communication technologies enabling each student to receive information not only in a text mode, but at the same time in a sound and visual display. In this regard teachers have unlimited opportunities of choosing assignments that contain different elements of classroom activity including multi-level training material.